Respostas

2014-05-04T10:01:02-03:00
X=-b+oumenos√b²-4ac÷2×a
x=3+oumenos√49÷10
x=3+oumenos7÷10
dessa forma as 2 raizes sao:
x=3+7÷10= 1
x=3-7÷10=-4÷10
1 1 1
2014-05-04T10:16:54-03:00
5x² - 3x - 2 = 0 ~> a = 5 , c = -3 , c = -2

primeiro se calcula o delta

Δ = b² - 4ac
Δ = (-3)² - 4.5.(-2)
Δ = 9 - (-40)
Δ = 49

x = -b ± √Δ
         2a

x = -(-3) ± √49
          2.5

x = ± 7
       10

x' = 3 + 7 = 10 = 1
        10      10

x" = 3 - 7 = -4  = -2        ou   x" = -0,4
        10      10     5
1 5 1